Antecedents of teachers’ professional competencies - Eva Ballová Mikušková; Marcela Verešová; Viktor Gatial (Cogent Education, 2024)
AbstractNon-behavioral factors potentially enhance the development of teachers’ professional competencies. Because there is a lack of research examining the direct relationships between teachers’ professional competencies and these non-behavioral factors, present study aimed to identify the main cognitive, personality and motivational antecedents of professional competencies among Slovak in-service teachers. The relationships between professional competencies, cognitive abilities (including executive functions, cognitive reflection and scientific reasoning), personality and motivation were measured in order to identify the main antecedents of teachers’ professional competencies. A total of 443 in-service teachers (88.7% women) aged 21–70 years old with 0 to 50 years of practice participated in the data collection. The main positive antecedents of professional competencies were having personality traits of agreeableness, conscientiousness and open-mindedness, having intrinsic and altruistic motivation and having developed executive function plans and time management. The main negative antecedent of professional competencies was the personality trait negative emotionality. It follows that these non-behavioral factors should be considered in the selection of student applicants and that more should be done to develop cognitive abilities during teacher training, including social psychological training.